2000
DOI: 10.1093/ndt/15.7.1000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the renin–angiotensin system and complications of insulin‐dependent diabetes mellitus

Abstract: In a Dutch IDDM population, including 69 patients with (incipient) diabetic nephropathy, the T-allele of the AGT-M235T polymorphism is associated with an elevated UAE and diabetic retinopathy and the CC-genotype of the AT1-A1166C polymorphism is associated with hypertension. A previously described interaction between the AGT-M235T and the ACE-ID polymorphisms could not be confirmed. Since the number of nephropathic patients in this study is small, these conclusions must be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 30 publications
3
30
3
Order By: Relevance
“…Apparently contrary to the present observations, no associations of AGT 235M/T polymorphism or interactions between AGT 235M/T, I/D ACE, or/and 1166A/C polymorphisms with regard to cardiovascular disease were found by van Ittersum et al (39) in the cross-sectional Dutch study comprising 257 subjects with type 1 diabetes. Surprisingly, in this study, the use of ACEIs was not included as a covariate in logistic regression analysis of CAD risk (39). Because in our study, the effect of RAS gene variants is highly related to ACEI/ARB treatment, we cannot be sure that the results of two studies are different.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Apparently contrary to the present observations, no associations of AGT 235M/T polymorphism or interactions between AGT 235M/T, I/D ACE, or/and 1166A/C polymorphisms with regard to cardiovascular disease were found by van Ittersum et al (39) in the cross-sectional Dutch study comprising 257 subjects with type 1 diabetes. Surprisingly, in this study, the use of ACEIs was not included as a covariate in logistic regression analysis of CAD risk (39). Because in our study, the effect of RAS gene variants is highly related to ACEI/ARB treatment, we cannot be sure that the results of two studies are different.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of genetic factors associated with premature coronary atherosclerosis in subjects with type 1 diabetes has not been intensively studied yet. To our knowledge, there is only one published study that analyzed the same genetic variants of RAS as evaluated in the present study (39). Apparently contrary to the present observations, no associations of AGT 235M/T polymorphism or interactions between AGT 235M/T, I/D ACE, or/and 1166A/C polymorphisms with regard to cardiovascular disease were found by van Ittersum et al (39) in the cross-sectional Dutch study comprising 257 subjects with type 1 diabetes.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, the important ones include existence of identifiable human disease from overexpression/mutations/polymorphisms in the renin, angiotensinogen, ACE, AT 1 R, aldosterone, and MR genes (Table 3). This is exemplified in a Dutch cohort with insulin-dependent diabetes mellitus (IDDM)-induced incipient diabetic kidney disease (336). Within this population, the T-allele of the AGT-M235T polymorphism is associated with increases in proteinuria, and the CC-genotype of the AT 1 -A1166C polymorphism is asso-ciated with hypertension.…”
Section: B Raas In the Kidneymentioning
confidence: 99%
“…There were no reports indicated a significant relationship between AGT rs699 and DR, but in patients with incipient diabetic renal failure the T allele of AGT rs699 was associated with DR. In these patients interaction between the D allele of ACE I/D and the T allele of AGT rs699 tended towards protection against DN (Van Ittersum et al, 2000). Oppose, other study indicated that the same interaction increases risk for DN in patients cu DR (Marre et al, 1997).…”
Section: Other Ras Genesmentioning
confidence: 83%